RESEARCH ON OPTIMAL DESIGN OF PLATE-WEB BEAM STRUCTURE AGAINST FATIGUE BUCKLING BASED ON PARETO GENERAL ALGORITHM - SU ShaoPu; XU GuangTao; DONG DengKe; CHEN An (Jixie qiangdu)
In virtue of Detail Fatigue Rating method（DFR）, an optimization design method of aircraft plate-web beam structure against fatigue buckling is proposed based on genetic algorithm. After finite element analysis and experimental verification, an optimized model of structure life on fatigue buckling is built by engineering method, and the structure design solution in the condition of minimum mass is achieved with maximum fatigue life. The theoretical results illustrated that the life can excessively increase than that of the original beam. This technology will provide the design strategy of reducing aircraft mass and cost production for general aircraft structure.